2019
DOI: 10.1021/acs.energyfuels.8b03861
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ca Additive Acting as a Deterrent to Na2CO3 Deactivation during Catalytic Coal Gasification

Abstract: The deactivation of Na 2 CO 3 , caused by the reaction between Na and Si and Al minerals in coal, is one of the key technical bottlenecks for the large-scale application of catalytic gasification. Ca can inhibit the deactivation of Na, and the binary Na−Ca catalyst shows strong synergistic effects during catalytic gasification. In this study, the deactivation behaviors of Na 2 CO 3 and the inhibition mechanism of Ca were systematically investigated by thermogravimetric, X-ray diffraction, Fourier transform inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…53,55−57 The priority of Ca over alkalis was also shown for Na when reacting with Si-or Al-minerals. 52 Second, the addition of Ca into the bed can have a dilution effect, which acts to improve the resistance of ash fusibility 24 or to form a less sticky ash coating 42 due to the increased Ca concentration in ash or layers. Bozaghian et al 58 compared the effectiveness of CaCO 3 in reducing agglomeration arising from straw using quartz sand and olivine as bed materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…53,55−57 The priority of Ca over alkalis was also shown for Na when reacting with Si-or Al-minerals. 52 Second, the addition of Ca into the bed can have a dilution effect, which acts to improve the resistance of ash fusibility 24 or to form a less sticky ash coating 42 due to the increased Ca concentration in ash or layers. Bozaghian et al 58 compared the effectiveness of CaCO 3 in reducing agglomeration arising from straw using quartz sand and olivine as bed materials.…”
Section: Discussionmentioning
confidence: 99%
“…These observations strongly suggest that, under steam gasification conditions, the addition of calcite has suppressed the reactions that would otherwise occur between olivine and K substances from grape marc. Previous studies have suggested that the two main anti-agglomeration mechanisms occur for Ca-based additives in a bed of silica sand. ,,,,, First, Ca behaves as a competitor of K during the interactions with silica to form Ca silicates and thus hinders the formation of low-melting-point K-silicates. ,, This is because Ca 2+ has a stronger affinity to negatively charged oxygen in the silica structure than K + . As a result, more K contents are released to the gas phase instead of being retained in the melts. , The priority of Ca over alkalis was also shown for Na when reacting with Si- or Al-minerals .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron powder (Fe), sodium carbonate, sodium aluminate, and potassium carbonate were ordered from Sinopharm Chemical Reagent Co. Shenmu (SM) coal, collected from the Shannxi province, was ground and sieved to a particle diameter of less than 125 μm, and corresponding char (SM) was prepared by the fast pyrolysis of SM coal. 17 The proximate and ultimate analyses of SM coal and SM char are shown in Table 1. SM was used as one basic carbon material to measure the catalytic performance of alkali.…”
Section: Methodsmentioning
confidence: 99%
“…11 A sodium−calcium binary catalyst has shown a better catalytic effect than the respective single component catalysts at 900 °C, and Ca acts as a good deterrent to Na deactivation. 12,13 Coals impregnated with alkali carbonates have shown promising results for coal gasification. 14 Composite catalyst consisting of sodium and iron has also been used as impregnation catalysts for coal gasification.…”
Section: Introductionmentioning
confidence: 99%